2021
DOI: 10.1002/jum.15690
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Abdominal Circumference Independently in the Diagnosis of Fetal Growth Restriction

Abstract: Objective-Society for Maternal-Fetal Medicine guidelines for diagnosing fetal growth restriction (FGR) have broadened the definition to include abdominal circumference (AC) <10 th percentile for gestational age (GA) regardless of estimated fetal weight (EFW). We aimed to compare the ability of three definitions of FGR to predict small for gestational age (SGA) neonates and adverse outcomes.Methods-We performed a secondary analysis of a prospective cohort of patients who underwent assessment of fetal growth bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…9 10 Previous data examining overall EFW <10 %ile for prediction of SGA birth weight has reported much lower positive predictive values (PPVs) of 49.4 to 63.7%. 11 12 A secondary analysis of a prospective cohort study demonstrated a PPV of 55.5% for detection of SGA birth weight among fetuses with either an AC or overall EFW <10th %ile. 12 Our data likely demonstrate higher rates of SGA birth weight due to inclusion only of fetuses with EFW <3rd %ile or AC <3rd %ile with overall EFW 3rd to 9th %ile.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 Previous data examining overall EFW <10 %ile for prediction of SGA birth weight has reported much lower positive predictive values (PPVs) of 49.4 to 63.7%. 11 12 A secondary analysis of a prospective cohort study demonstrated a PPV of 55.5% for detection of SGA birth weight among fetuses with either an AC or overall EFW <10th %ile. 12 Our data likely demonstrate higher rates of SGA birth weight due to inclusion only of fetuses with EFW <3rd %ile or AC <3rd %ile with overall EFW 3rd to 9th %ile.…”
Section: Discussionmentioning
confidence: 99%
“…Different research also examined the ability of AC in detecting SGA and fetal growth restriction. They found that AC below the 10 th percentile can be used to diagnose FGR [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other alternative criteria for the definition of FGR include prenatal diagnosis of abdominal circumference below the 10th, 5th, or 3rd percentile 1 . Notably, there are several studies with conflicting results aiming to determine, in a low‐risk population, which of the ultrasound parameters would be the better parameter in predicting neonates with FGR, abdominal circumference below the 10th percentile, estimated fetal weight below the 10th percentile, 2 or combined measurements 3 . Nevertheless, it has been suggested that the definition of FGR may be too broad, leading to false‐positive diagnoses with small for gestational age (SGA) infants who are constitutionally small and healthy 3 …”
Section: Introductionmentioning
confidence: 99%
“…abdominal circumference below the 10th percentile, estimated fetal weight below the 10th percentile, 2 or combined measurements. 3 Nevertheless, it has been suggested that the definition of FGR may be too broad, leading to false-positive diagnoses with small for gestational age (SGA) infants who are constitutionally small and healthy. 3 In order to reduce adverse neonatal morbidity and mortality, accurate identification is important together with proper timing of delivering.…”
mentioning
confidence: 99%
See 1 more Smart Citation